Multi-objective optimization of user capacity for WPCN - Sharma, S.; Yoon, W. (International Journal of Engineering Research and Technology, 2019)
In this paper our goal is to maximize the individual user capacities of massive multi-input multi-output (MU-MIMO) systems through wireless powered communication network (WPCN). A multiple-objective optimization approach (MOOP) is developed while guaranteeing the quality of service (QoS) requirement. A new concept is proposed to derive Pareto solution via weighted Tchebycheff method from an equivalent single-objective optimization problem (SOOP) that minimizes the maximum of several quasiconvex fractional functions by iterative algorithm. The simulation results show that the proposed algorithm has the optimal performance and the user capacity of the distributed massive (DM) multi-input multi-output (MIMO) is considerably higher than that of the centralized massive (CM)-MIMO system.
Keywords: Multiobjective optimization; Pareto optimal; Quasiconvex; Wireless powered communication networks